The Diocese of Baloie (Ecclesia Baloiensis) - Škegro, Ante (Arheološki vestnik, 2007)
The early Christian period in the mainland of the Eastern Adriatic is still mainly unknown even though research has been carried out for more than one hundred years. Major difficul-ties come forward particularly when trying to determine, with reasonable precision, the earliest ecclesiastical organisation, boundaries of singular dioceses and parishes, their original names, sites of cathedral churches, names of their bishops, priests or deans etc. The best example to illustrate this is the Diocese of Baloie (Ecclesia Baloiensis), which is the subject of this paper. Numerous problems related to it arise also from the Acts of the Church councils held in Salona in 530 and in 533 AD, presided by the Salonitan archbishop Honorius Iunior. The 15th and the 16th century manuscript copies provide us with numerous controversial data and rather unclear names. Further difficulties arise from the scarcity of adequate epigraphical or written sources to compare with the data supplied by the Acts of the Salonitan councils. However, there are numerous traces of the early Christians in these regions, manifested amongst others by the remains of early Christian basilicas, baptisteries, vaulted tombs, sarcophagi with crypto-Christian or Christian symbols, as well as inscriptions and small objects for everyday use.